Pengaruh Good Corporate Governance dan Ukuran Perusahaan Terhadap Manajemen Laba (Studi Empiris pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang terdaftar di BEI Periode 2019-2021) - Dinda Marisha; Haninun (Jurnal EMT KITA, 2023)
The purpose of this study is to explore the impact of corporate governance measures on revenue management in the Indonesia Stock Exchange's manufacturing industry, especially the food and beverage sub-sector, over the period 2019-2021. Independent variables investigated included management ownership (X1), audit committee (X2), board composition (X3), and company size (X4). The study population consisted of 810 companies listed on the Indonesian Stock Exchange during the above period. The study used a targeted sampling method to collect samples from 11 companies that met the study criteria. Data analysis was performed using the multiple linear regression method. The findings of this study show that management ownership, audit committee and board composition, and company size have a significant and negative impact on revenue management. The conclusion of the findings is that good corporate governance practices are important to influence the revenue management of manufacturing companies on the Indonesia Stock Exchange. This study provides a deeper understanding of the relationship between corporate governance and revenue management variables and provides guidance for companies to optimize their corporate governance practices to achieve their sustainable long-term goals,